Options for Strengthening Social Safety Nets in Lao PDR : A Policy Note - World Bank (Washington, DC, 2013)
The Government of Lao PDR (GoL) announced that its 7th national socio-economic development plan, covering 2010 through 2015, will focus on achieving the Millennium Development Goals by 2015 and exiting least developed country status by 2020. To achieve these goals, one of the priority areas in the 7th National Socio-Economic Development Plan (NSEDP) is to reduce vulnerability to shocks by providing and improving social safety nets (SSN). As part of this ongoing work a SSN Workshop was organized in Vientiane in March 2010, with the following five objectives: 1) improve joint understanding of the current social protection system (focusing on SSNs); 2) learn from government about their development priorities for 2011-2015; 3) learn from government and donors about their experiences with social protection and poverty reduction programs; 4) discuss various SSN options and identify which options are appropriate in the current context and given current priorities; 5) identify potential ways that donors and development partners can work together to strengthen SSNs in Lao PDR. This brief note summarizes the findings from the SSN workshop, and potential next steps.